THE MAIN PROPERTY OF PROPORTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Proportion is one of the fundamental concepts in mathematics, particularly in the fields of arithmetic, algebra, and geometry. The main property of proportion states that in any equality of two ratios, the product of the means is equal to the product of the extremes. This seemingly simple principle has vast applications across various branches of mathematics, science, and real-life problem-solving, ranging from geometry and trigonometry to economics and physics. This article aims to provide a comprehensive discussion of the main property of proportion, starting from its historical development, mathematical definition, and proof,